the PENEGAKAN STRICT LIABILITY PADA KASUS HUKUM LINGKUNGAN DI INDONESIA (Studi Kasus Putusan Nomor 125/Pdt.G/2016/PN.Bjm Dan Putusan Nomor 139/PDT.G-LH/2016/PN Jmb): PENEGAKAN STRICT LIABILITY PADA KASUS HUKUM LINGKUNGAN DI INDONESIA (Studi Kasus Putusan Nomor 125/Pdt.G/2016/PN.Bjm Dan Putusan Nomor 139/PDT.G-LH/2016/PN Jmb) - Elfi Tumangger, Nola; Rahmi, Elita; Hartati, Hartati (Fakultas Hukum Universitas Jambi, 2024)
Enforcement law environment No can do with prevention and action preventive, for example, effort enforcer law prevent happen pollution environment life but can be done in a way repressive is effort enforcer law do action law to who violated it provisions current regulation. Principle strict liability is basic things in straightening up justice through something decisions in related courts with pollution environment, however, it can seen that For deeper with exists a second difference in the decision that, so in matter This the judge's consideration is absolute decision, if in something case Already No do effort law in case the. In researching this article, the author focuses on Enforcement penalty administration as An instrument enforcement law environment that has important meaning related to its function as instrument control, prevention, and overcoming acts prohibited by the provisions environment life. Through penalty administration intended for action violation That stopped, so penalty administration is instrument juridical in nature non- judicial preventive and depressive For end or stop violation the provisions listed in condition protection and management environment live with study two decision different courts to case fire land that has been through a trial process and enforceable law fixed (encroach), meanwhile method research used in this article is study exists problem norm laws and regulations current regulation. With So, the end of this article will contribute the main ideas to the enforcement law environment in field penalty administration from revocation frequent permission occurs in cases environment in Indonesia.